The Work Life Balance and Job Satisfaction in Oil and Gas organisations in the UAE context - Al Sumaiti, Rashed Saad (2010)
Work life balance (WLB) is an important topic of human resource management and has become a top priority for workers everywhere. Some organisations trying to attract and retain their valued employees by implementing and managing WLB programs and policies. The purpose of this study is to examine the factors related to work life balance and job satisfaction. It will explore the impact of open office environment, telework and work life balance on job satisfaction in the Oil and Gas organisation in the United Arab Emirates. The main objectives of this study are: to investigate the influence of the open office environment on employees’ satisfaction, to examine the relationship between telecommuting and job satisfaction, to identify good work flexibility arrangements that can lead to job satisfaction, to examine the relationship between Work Life Balance and job satisfaction and lastly to provide a list of recommendations that could help the organisations and employees to achieve a better work life balance and job satisfaction. A self-administered questionnaire was distributed randomly to a sample of 195 full-time employees used in this study and data collected accordingly. The findings show that Work Life Balance (WLB) is significantly and positively correlated with job satisfaction. In addition, telework and an open office environment have a positive correlation with job satisfaction. The importance of providing good WLB arrangements within an organisation is highlighted in the recommendations to improve employees’ satisfaction, enhance their performance, and collaboration and hence increase productivity.